2017
DOI: 10.14218/jcth.2016.00060
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir Use in the Setting of End-stage Renal Disease: A Single Center Experience

Abstract: Background and Aims: Patients with chronic hepatitis C (CHC) and end-stage renal disease (ESRD) who are dialysisdependent form a unique group, in which safety, tolerability and efficacy of sofosbuvir (SOF)-based direct-acting antivirals (DAAs) need further evaluation. Methods: We performed a retrospective analysis of 14 patients with CHC and ESRD on dialysis who received 15 courses of SOF-based therapy. We evaluated dose escalation to standard-dose SOF in this proof-of-principle experience. Results: Sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Recent literature regarding the efficacy of DAAs in patients co‐infected with HIV/HCV also has high rates of cure with SVR rates of 91%‐94% . Likewise, patients on haemodialysis in our study were found to have an overall SVR of 93%, which is comparable to prior studies reflecting high response rates in this population . SVR rates were lowest in GT1 patients treated with SOF+SIM (75%‐83%), although this may be a reflection of our small number of haemodialysis patients, as prior studies have suggested better response rates with this regimen in other cohorts .…”
Section: Discussionsupporting
confidence: 77%
“…Recent literature regarding the efficacy of DAAs in patients co‐infected with HIV/HCV also has high rates of cure with SVR rates of 91%‐94% . Likewise, patients on haemodialysis in our study were found to have an overall SVR of 93%, which is comparable to prior studies reflecting high response rates in this population . SVR rates were lowest in GT1 patients treated with SOF+SIM (75%‐83%), although this may be a reflection of our small number of haemodialysis patients, as prior studies have suggested better response rates with this regimen in other cohorts .…”
Section: Discussionsupporting
confidence: 77%
“…of patientsNo. of dialysis recipientsHistory of Cirrhosis (%)mean/median baseline RNAGenotypeSOF-based regimenDose of SOFSVR12/24 (PP)NOS scoreAggarwal (2017) [19]USA141420% (F3,F4)8,375,588.6 IU/MLGT1–60%, GT2–6.7%, GT3–20%, GT4–13.3%SOF + SMV, SOF + RBV, SOF/LDV ± RBV, SOF + PR, SOF + DCV12–24 W200 mg QD92.8% 13/144Akhil (2018) [26]India2222NA2,642,495 IU/MLGT1–63.63%, GT3–27.27%,GT4–9%SOF + RBV 12 W400 mg QD80% 16/204Beinhardt (2016) [27]Austria101040% (30% decompensation)6.1 ± 0.8log IU/MLGT1a-20%, GT1b-40%, GT3a-20%,GT4–20%SOF + PR,SOF + SMV,SOF + DCV, SOF + RBV 12–24 W400 mg QD90% 9/104Bera (2017) [20]India252520%6.4 ± 0.57log IU/MLGT3–72%, GT1–24%,GT4–4%SOF + DCV 12–24 W400 mg/48 h100% 16/164Bhamidimarri (2015) [31]USA151260%9.7 × 10 6 IU/MLGT1a-67%,GT1b-33%SOF + SMV 12–24 W200 mg QD or 400 mg/48 h87% 13/154Butt (2108) [45]USA137NANANANASOF/LDV ± RBV 12–16 W400 mg QD95% 103/1083Choudhary (2017) [21]India161612.50%7 (5–8)log IU/MLGT1–69%,GT3–25%,GT-6%SOF + PR, SOF + DCV ± RBV12 W400 mg/48 h80% 8/104Desnoyer (2016) [32]France121283%6.59 (6.13–6.86)log IU/MLGT1–92%GT2–8%SOF + SMV, SOF + DCV, SOF/LDV, SOF + RBV 12–24 W400 mg QD or 400 mg TIW83% 10/125Dumortier (2017) [18]France503554%2,603,063 IU/ML…”
Section: Resultsmentioning
confidence: 99%
“…Such case series have generally reported favorable efficacy and safety. However, the results are often limited by the small number of patients . In a meta‐analysis with data pooled from 11 different studies comprising a total of 264 patients, the excellent efficacy and safety of sofosbuvir‐based therapies in patients with severe renal impairment has been demonstrated …”
Section: Introductionmentioning
confidence: 99%